An assessment of the status of psylloid species (Hemiptera: Psylloidea) as potential pests of commercial citrus in southern Africa: implications for pest management - Moagi, Raynold (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Psylloids (Hemiptera: Psylloidea), constitute a group of plant sap-sucking insects, some of which are economically significant pests in different ecosystems due to their potential to transmit Gram-negative bacteria, such as the Candidatus Liberibacter species. The African citrus triozid (ACT), Trioza erytreae (Del Guercio), which transmits African citrus greening and the Asian citrus psyllid (ACP), Diaphorina citri Kuwayama, which transmits Asian citrus greening are significant threats to citrus. Asian citrus psyllid poses a global economic threat due to its ability to vector "Candidatus Liberibacter asiaticus" (CLas), which can rapidly kill citrus trees. However, both ACP and CLas are currently not present in southern Africa but are present in East and West Africa. In the Afrotropical region, 71 triozid species are known to occur and approximately 41 described Diaphorina species in southern Africa. Currently, two indigenous Diaphorina species, Diaphorina punctulata and Diaphorina zebrana have been documented to feed on citrus. There is a significant knowledge gap regarding the ecological roles of other indigenous psylloid species occurring within the citrus environments. Therefore, this study aimed to: (i) determine the diversity and community structure of psylloid species in citrus environments, and (ii) their host ranges through DNA analysis of gut contents to determine if they fed on citrus. Field surveys were carried out across 12 distinct commercial citrus environments across Limpopo and Mpumalanga provinces between 2022 and 2023. Psylloids were collected using yellow sticky traps and an insect sweep-net. Collected psylloid specimens were preserved in 70% ethanol vials and identified to the lowest possible taxonomic level (i.e. genus or species) using both published and unpublished dichotomous identification keys. Furthermore, citrus leaf samples were collected from the same plants on which psylloids were found in the orchards. Genomic DNA (gDNA) was extracted from both leaf and psylloid samples using two different DNA extraction methods. To confirm if citrus DNA could be detected in the psylloid guts, all leaf gDNA samples were initially amplified using the rbcLaF/R primer pair, targeting a 530-bp region of the chloroplast rbcL gene through the polymerase chain reaction (PCR). Lastly, gut content analysis was performed on 11 psylloid species using the same primer pair through PCR to detect citrus DNA. A total of 4,900 psylloids belonging to five families (i.e. Aphalaridae, Carsidaridae, Liviidae, Psyllidae and Triozidae), 19 genera and 47 species, were collected in citrus environments. More psylloids were recorded in Limpopo (3,754) than in Mpumalanga (1,146). The most abundant species were Pauropsylla trichaeta (1,680), followed by Diaphorina punctulata (466), Trioza erytreae (426), Diaphorina virgata (371), Euryconus sp. (358), Cacopsylla sp. (311), Retroacizzia mopanei (263), Acizzia russellae-group (240), Acizzia sp.3 (216) and Acizzia sp.2 (140). Yellow sticky traps captured 3,265 psylloids in citrus orchards, while an insect sweep-net collected 1,635 psylloids (477 from citrus orchards and 1,158 from adjacent natural vegetation). Data from the insect sweep-net revealed that 22 psylloid species were recorded on citrus. In comparison, nine psylloid species were found on Vachellia spp. and unidentified plant species separately, whereas six, three and two psylloid species were recorded on marula, Ficus sp. and mopane, respectively. The abundance, richness and community structure of psylloids differed significantly between the collection methods, provinces and among plant species. The rbcLaF/R primer pair amplified all citrus leaf gDNA samples, producing amplicons of the targeted 530-bp size. The PCR analysis of 11 psylloid species showed that the rbcLaF/R primer pair amplified plant DNA, with PCR-amplified plant DNA samples producing amplicons between 500-bp and 750-bp in the gut contents of five psyllid species: Diaphorina punctulata, Diaphorina virgata, Diaphorina zebrana, Euryconus sp. and Trioza erytreae. However, the targeted 530-bp plant DNA region was only amplified from the gut contents of Euryconus sp. and Diaphorina punctulata. This study documented psylloid diversity and community structure within commercial citrus environments. The findings indicate that the community of psylloids was diverse in citrus environments, with yellow sticky traps being more effective in monitoring different psyllid species within these environments. Furthermore, the PCR analysis detected citrus DNA in the gut contents of Euryconus sp. and Diaphorina punctulata, suggesting that they could be nibbling on citrus when their specific or main host-plants adjacent to citrus orchards are depleted. However, these insects do not lay their eggs or complete their life cycle on citrus, further confirming that citrus is not their host-plant. Thus, further studies, including Sanger sequencing of PCR-amplified plant DNA, are recommended to confirm the ingested plant species, and host-specific testing including infection trials needs to be conducted.
Keywords: Citrus Diseases and pests -- South Africa; Candidatus Liberibacter; Psylloidea; Polymerase chain reaction; Insect trapping Equipment and supplies; Pests Control